A nippuri szegény ember meséje és a Ludas Matyi ó-romániai népmese-mintájának kérdése - Julow, Viktor (1963)
About the Pattern of “The Tale of the Poor Man of Nippur” and of the Old-Rumanian Folk Tale “Ludas Matyi”; engl. Zusammenfassung.